Cardiac Function in Long-Term Survivors of Childhood Lymphoma - Mark K. Friedberg; Ido Solt; Myriam Weyl-Ben-Arush; Yulia Braver; Avraham Lorber (Cardiology Research and Practice)
Objectives. We studied long-term effects of therapy for childhood lymphoma on cardiac function. Design and patients. We prospectively evaluated 45 survivors of childhood lymphoma, using clinical parameters, electrocardiography and echocardiography. Further comparisons were made between lymphoma subgroups and between males and females. Results. Mean age at diagnosis was 9.1 years. Mean followup duration was 10.9 years. The NYHA functional class was I in 43 patients and II in 2 patients. A prolonged QTc interval (>0.44 msec) was found in 8 patients. Left ventricular (LV) systolic function and compliance were normal (LV shortening fraction 40±5.6%; cardiac index 2.84±1.13 L/min/m2; E/A wave ratio 2.5±1.3; mean ± S.D.), LV mass was normal (97±40 grams/m2, mean ± S.D.). Mitral regurgitation was observed in 7/45 patients (16%). Asymptomatic pericardial effusions were found in 3/45 (7%) patients. Conclusions. Long-term follow-up shows that most parameters of cardiac function are normal in survivors of childhood lymphoma. This is likely due to relatively low doses of anthracyclines in modern protocol modalities. Abnormalities in mitral valve flow, QTc prolongation and in a small proportion of survivors, and functional capacity necessitate long-term cardiac follow-up of these patients.